A community- based study of the prevalence and risk factor for “Schistosoma haematobium” in Two Endemic Districts of Taiz Governorate, Yemen - Al-Kabab, Abdullnasser Ahmed; El-Sheikh, Einas Ibrahim; Al-Mikhlafy, Abdulla Abdu (Journal of medical and pharmaceutical sciences, 2023)
Background: Schistosomiasis is still a major public health problem despite launching preventive chemotherapy campaigns (using Praziquantel) through yearly treatment of school-age children since 2008. Objective: To conclude: prevalence, contributing factors, intensity for Schistosoma Haematobium in Al-Shmaytin & Al-Mwaset districts-Taiz, Yemen. Methods: a cross-sectional study, data on age, sex, marital status, income, education, location, water contact, medical history (MH), urine test results (filtration method used to detect S. haematobium &concentration methods for the detection of infection intensities), were gathered using structured questionnaires between March & April 2021. Sample size calculated using appropriate formula. 298 individuals selected by systematic random sampling. Informed consent obtained. For statistical analysis, SPSS version 24 is used. For “p”-values, the statistical significance was set at 0.05. Results: S. haematobium was found in 17 of 273 respondents, with a prevalence of 6.2%, higher in Al-Shmaytin (9.2%) than in Al-Mwaset (3.5%), and a light-intensity 59%. Adjusted Odds Ratio (AOR) for the following variables (95% confidence interval (CI)): district 3.7 (12 cases from Al-Shmaytin 9.2%), age 1.0 (13 cases from 6-18 years 7.8%), sex 2.8 (13 cases from female 7.4%), marital 0.3 (15 cases from single 8%), educational status 1.3 (15 cases from Illiterate/Essential School 6%), swimming/bathing 2.0 (13 cases 8.6%), wear shoes 0.4 (15 cases from those who do not wear shoes 8.1%), urinate near water 1.7 (8 cases 9.8%), family member with disease 1.0 (5 cases 7.1%), dysuria 1.7 (8 cases 8.3%), and receiving anti-schistosomiasis drugs 0.9 (9 cases among those didn’t receiving drugs 7%). All had low monthly incomes and no sanitation. Prevalent among: secondary school and higher (2, 8.7%), unaware of schistosomiasis (15, 7.4%), and unaware of prophylaxis (16, 7.1%). Conclusions: Hypo-endemic urinary schistosomiasis in study areas. Most patients from Alsafiah, females, 6-18 years, light-intensity, swimming/bathing, single, didn't receive Praziquantel®, urinated near water, had dysuria, didn't wear shoes, had diseased family members, lacked sanitation, were unaware of schistosomiasis and its prevention, lived near water sources, and had low monthly income.
Keywords: S. haematobium; epidemiology; questionnaire; hematuria; egg positive rate; infection intensity; water-contact pattern; factors; rural areas; Yemen